Characteristics of the Children's Revised Impact of Event Scale in a Clinically Referred Dutch Sample. Issue 3 (2nd May 2014) - Verlinden, Eva; van Meijel, Els P. M.; Opmeer, Brent C.; Beer, Renée; de Roos, Carlijn; Bicanic, Iva A. E.; Lamers‐Winkelman, Francien; Olff, Miranda; Boer, Frits; Lindauer, Ramón J. L.
<x xml:space="preserve">Abstract</x> Early identification of posttraumatic stress disorder (PTSD) in children is important to offer them appropriate and timely treatment. The Children's Revised Impact of Event Scale (CRIES) is a brief self‐report measure designed to screen children for PTSD. Research regarding the diagnostic validity of the CRIES is still insufficient, has been restricted to specific populations, and sample sizes have often been small. This study evaluated the reliability and validity of the 8‐item (CRIES‐8) and 13‐item (CRIES‐13) versions of the CRIES in a large clinically referred sample. The measure was completed by 395 Dutch children (7–18 years) who had experienced a wide variety of traumatic events. PTSD was assessed using the Anxiety Disorders Interview Schedule for DSM‐IV: Child and Parent version. A cutoff score of 17 on the CRIES‐8 and 30 on the CRIES‐13 emerged as the best balance between sensitivity and specificity, and correctly classified 78%–81% of all children. The CRIES‐13 outperformed the CRIES‐8, in that the overall efficiency of the CRIES‐13 was slightly superior (.81 and .78, respectively). The CRIES appears to be a reliable and valid measure, which gives clinicians a brief and user‐friendly instrument to identify children who may have PTSD and offer them appropriate and timely treatment.